Fiscal consolidation and its growth effects in euro area countries: Past, present and future outlook - Philipp Heimberger (The Vienna Institute for International Economic Studies (wiiw), 2024)
This paper is about fiscal consolidation measures (i.e. tax hikes and government spending cuts motivated by a desire to reduce the fiscal deficit and public debt) in euro area (EA) countries. The focus is on analysing the growth effects of fiscal adjustments as well as their implications for debt sustainability assessments. I discuss the size and composition of fiscal consolidation by distinguishing three periods: the run-up to the EA, when governments faced the Maastricht criteria for joining the monetary union (1992-1998); before and during the recession triggered by the global financial crisis (1999-2009); and the euro crisis (with a specific focus on the 2011-2013 period). The empirical evidence on the growth effects of fiscal consolidation shows that while fiscal adjustments are contractionary, the negative growth effects were particularly strong and persistent during the euro crisis. With regard to the austerity outlook, I show that, beginning in 2025, EA countries are set to implement fiscal consolidations over multiple years so as to meet reformed EU fiscal rules. The adjustment requirements for some member countries are large in historical comparison. The paper argues that the framework for debt sustainability analysis at the heart of the reformed EU fiscal rules downplays the domestic growth impacts of fiscal adjustments and ignores cross-country spill-overs that magnify domestic growth effects. In all likelihood, the reformed framework underestimates the negative growth effects of fiscal consolidation. I conclude that implementing the multi-year fiscal adjustments required to meet EU fiscal rules may not reduce public debt ratios across the EA's member countries, as the European Commission expects, and that the economic and political implications of austerity may complicate the governance of a fragile EA.
Keywords: H30; H63; O47; 330; Fiscal policy; fiscal consolidation; fiscal multiplier; growth; public debt; euro area